Haploidentical Stem Cell Transplantation With Dual Source of Cells and Post‐Transplant Cyclophosphamide - Ana Marcela Rojas Fonseca‐Hial; Katya Parisio; Jose Salvador Rodrigues deOliveira (Cancer Medicine, 2025)
ABSTRACT Background Dual sources of cells (DSC) with peripheral blood stem cell apheresis (PBSC) and surgical bone marrow (BM) for haploidentical hematopoietic cell transplantation (Hid‐HCT) are used in China and some Asian countries. The experience of the Baltimore group for haploidentical transplant with post‐transplant cyclophosphamide (PT‐Cy) and reduced‐intensity‐conditioning (RIC) regimen used BM as a source of hematopoietic stem cells. Methods We retrospectively analyzed 64 Hid‐HCT with DSC and PT‐Cy, RIC (n = 57), or myeloablative‐conditioning (MAC) (n = 7), from two public health Brazilian centers, with a median follow‐up of 23.3 months (6.7–45.4). Results The 49 malignant patients were 27/46 (58.7%) beyond the first remission or with no complete response, and three patients did not complete disease status evaluation before transplant. Eight of 62 patients (12.9%) had grade 2 or more Hematopoietic Cell Transplantation‐Specific Comorbidity Index (HCT‐CI), and two patients had no HCT‐CI classified. Cytomegalovirus (CMV) viremia occurred in 26 of 57 (45.6%). The cumulative incidence of 100‐day grade III‐IV acute GVHD was 12.3% (7/57), with a 95% confidence interval (CI) of 3.8% and 20.8%, and 2‐year moderate or severe chronic GVHD was 21.1% (11/52; 95% CI, 10.1%–32.3%). The 2‐year relapses were 24.5% for malignant disease (12/49; 95% CI, 12.4%–36.5%). The 2‐year overall survival (OS) probability was 54.7% (35/64; 95% CI, 42.5%–66.9%). Benign diseases achieve 2‐year OS in 73.3% (11/15; 95% CI, 51%–95.7%) of the patients. The HCT‐CI were significant in multivariate analyses for DFS (p = 0.002) and OS in uni‐ and multivariate analyses (both p < 0.001). The number of CD34+ cells by apheresis collection was significant in multivariate analysis for DFS (p = 0.039). Conclusion Hid‐HCT using PT‐Cy, DSC, and RIC is a safe option for benign and malignant diseases.